The need to manage a foreign language in order to generate economic, social and cultural development in our country (2016)
There is a concern about the economic situation of our country, the low rates of employment and the need for a comprehensive education that is based on the development of thought and the pursuit of knowledge in the community. Given these concerns, this thesis proposes to show the impact that brings a foreign language as a factor that can be a catalyst and promoter of economic, social, cultural development. However, this conception a little complex, are rooted variety of contexts-cultural, social, and economic, to be able to finally answer the question based on the need and the impact that leads managing a second language in these aspects. As technology and the economy going forward, the need to learn another language becomes vital; therefore, it can be argued that it is a matter of lack of resources, such as the time and financial investment, the reasons for which the user will be able to decide about the necessity of learning a second language or not.